Integrasi Praktikum Sederhana dalam Model Inkuiri Terbimbing: Dampaknya Dalam Meningkatkan Hasil Belajar Siswa - Hendrik Pratama; Izzul Isnaini Lathif (Lembaga Bale Literasi, 2025)
Science is one of the subjects that students still fear and dislike. In the sample studied, it shows that the average student learning outcomes are below the KKM. This is caused by the lack of student interest in learning due to the lack of teacher innovation in using learning models and media. This study aims to determine the application of the guided inquiry learning model as an effort to improve learning outcomes in science subjects in grade 9 students of SMP Negeri 2 Rejoso in the 2024/2025 academic year. The type of research used is Classroom Action Research (PTK). The research subjects were class 9-A students totalling 27 people who were taken by random sampling technique. Data collection techniques in the form of learning outcomes test data, observation, and documentation. Learning outcomes using guided inquiry in cycle I averaged 69.25 with the category ‘sufficient’ while cycle II increased with an average of 87.40 with the category ‘very good’. This study was able to reveal that the use of simple practicum media around students is able to change the paradigm that science can be learned from everything around. Practical activities make students able to work together, find problems to find solutions, and be able to build active communication between students and teachers.